Strategi Manajemen Public Relations dalam Mempertahankan Loyalitas Pelanggan - Aziz Setiyawan; Husen Fahmi; Ani Yuningsih (UNISBA Press, 2022)
Abstract. In today, the creative wedding business is very strong, one of which is wedding organizer. The trend of organizing events also continues to grow. Organizing an event that is